Flavour characteristics of Piper betle L. - A K S RAWAT, V R BALASUBRAHMANYAM, (Journal of Spices and Aromatic Crops, 1992)
The betel leaves are aromatic with varied taste ranging from sweet to pungent due to the presence of essential oil. Compounds that contribute to the pungency flavour and stimulating properties of the leaf are of interest to the flavour industry. The results of investigations carried out so far on the chemical analysis of essential oil of betel leaves have been reViewed. The results of the gas chromatography and mass spectrometry (GCMS) of the oil of all the five recognized varieties of Piper betle are discussed. The yield and composition of essential oil of betel leaves have been influenced by age and position of the leaf on the stem, season of harvest, potassium nutrition etc. Promoting the use of this important essential oil in flavour industry and confectionerles so as to utilise the surplus leaves from the assembling and wholesale markets which will otherwise go waste is suggested.